2020
DOI: 10.1002/hep.31249
|View full text |Cite
|
Sign up to set email alerts
|

The IKKβ‐USP30‐ACLY Axis Controls Lipogenesis and Tumorigenesis

Abstract: Background and Aims Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related death that develops as a consequence of obesity, cirrhosis, and chronic hepatitis. However, the pathways along which these changes occur remain incompletely understood. Approach and Results In this study, we show that the deubiquitinase USP30 is abundant in HCCs that arise in mice maintained on high‐fat diets. IKKβ phosphorylated and stabilized USP30, which promoted USP30 to deubiquitinate ATP citrate lyase (ACLY) and fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 50 publications
5
70
0
Order By: Relevance
“…Knockdown of USP30 significantly decreased basal respiration as well as oxygen consumed during oxidative phosphorylation (+ Oligomycin; Figure 1F). Reduced respiration is in agreement with a recent study in primary hepatocytes from USP30 knockout mice (Gu et al, 2020). In conclusion, we showed that genetic knockdown of USP30 can increase mitophagy as indicated by the increased mitoKeima signal but may also affect distinct aspects of mitochondrial function in the SHSY5Y cells.…”
Section: Knockdown Of Usp30 Enhances Mitokeima Signal In Shsy5y Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…Knockdown of USP30 significantly decreased basal respiration as well as oxygen consumed during oxidative phosphorylation (+ Oligomycin; Figure 1F). Reduced respiration is in agreement with a recent study in primary hepatocytes from USP30 knockout mice (Gu et al, 2020). In conclusion, we showed that genetic knockdown of USP30 can increase mitophagy as indicated by the increased mitoKeima signal but may also affect distinct aspects of mitochondrial function in the SHSY5Y cells.…”
Section: Knockdown Of Usp30 Enhances Mitokeima Signal In Shsy5y Cellssupporting
confidence: 93%
“…The absence of these proteins from the inner mitochondrial membrane could result in a compromised ETC and that could lead to reduced respiration. Another study by Gu et al has reported reduced OCR in primary hepatocytes from USP30 knockout mice where they identified that USP30 can be phosphorylated by IKKβ, resulting in deubiquitination of ATP citrate lyase and fatty acid synthase (Gu et al, 2020). Both our results and the study from Gu et al indicate that USP30 could potentially regulate different metabolic pathways such as ATP production and lipogenesis.…”
Section: Discussionsupporting
confidence: 72%
“…CUL3-KLHL25 E3 ligase can inhibit lipid synthesis and tumor growth by targeting ATP citrate lyase (ACLY) for ubiquitination and proteolysis [278]. However, USP13 and USP30 can mediate deubiquitination of ACLY, increasing the stability of ACLY to promote development of ovarian cancer and hepatocellular carcinoma, respectively [271,279]. TRB3-COP1 mediates proteolysis of acetyl-coenzyme A carboxylase (ACC) in ubiquitin-dependent manner, inhibiting fatty acid synthesis and stimulating lipolysis [280].…”
Section: Ubiquitination and Fatty Acid Metabolismmentioning
confidence: 99%
“…USP14 directly interacts and stabilizes FASN, followed by elevated triglyceride accumulation 20 . Additionally, USP30 deubiquitinates and stabilizes ACLY and FASN and plays important roles in lipogenesis and HFD-driven HCC 8 . Interestingly, we also observed the differential expression of USP13 and USP14 in HCC tissues, but the difference in USP22 expression was more signi cant than that in USP13 and USP14 (Fig.…”
Section: Discussionmentioning
confidence: 99%